P3.292 The 2013 IUSTI European Collaborative Clinical Group (ECCG) Report on the Diagnosis and Management of Chlamydial Infections in Europe. (13th July 2013) - Brooks, B; Banks, J; Ison, C; Laar, M van de; Moi, H; Radcliffe, K; Unemo, M; Ross, J; White, J; Patel, R
Abstract : Background: The European Collaborative Clinical Group (ECCG) is an expanding network of over 120 Sexually Transmitted Infection specialists from 36 European countries, who collaborate to conduct questionnaire based research across the European Region to identify variations in practise and inform development of international evidence-based guidelines for diagnosis and management of STIs. The use of sensitive and specific assays and widespread screening has identified clearly the substantial burden of chlamydial infections across Europe. Infection remains common, despite established screening and treatment programmes in many European countries. Recent data has recently challenged the effectiveness of opportunistic screening and standard short course azithromycin therapy and guidance on tests of cure and partner management remain controversial. Method: The 2013 ECCG survey focuses on the diagnosis and management of chlamydial infection. An online survey constructed around clinical scenarios is gathering data on the type of test, site of testing, use of sample pooling and treatment choices. Follow up, including tests of cure and partner management is also being assessed. Results: Interim analysis of results to date show considerable variation in most of the areas studied. Despite their clear advantage many European populations are still denied the benefits of NAATs based testing. Importantly first line antibiotic choice varies as do test pooling strategies and timing and frequency of tests of cure. The survey is currently running and complete data will be available in late spring for full reporting at the conference. Conclusion: As in previous successful ECCG surveys the 2013 ECCG survey on the diagnosis and management of chlamydial infections includes a particular focus on areas where international guidance is currently lacking or poorly detailed. The ECCG has also recently expanded into parts of Eastern Europe and will be able to present data on STI care from this area for the first time.